UNITY AND IDENTITY IN EVANGELICALISM AND PROSPECTS FOR BRIDGE BUILDING WITH THE ORTHODOX CHURCH - WOODS, Paul (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
This paper reflects on unity and identity within evangelicalism, briefly tracing the development of the movement within Protestantism before sketching its current situation. From the very beginning of Protestantism, concepts such as authority, scripture, and church, and their relations to individual believers have been complex. Five hundred years after the Reformation, the unity of the movement has come under increasing strain. Evangelicals have been buffeted by the modernist influence of the Fundamentalist-Liberal controversy in the United States, the advent of postmodernity, and a developing sense of unease within, although their numerical strength and global representation have continued to increase. Current issues facing evangelicalism include authority in the church, relations with political causes, and relevance to our pluralistic modern world; responses to such challenges reflect the internal diversity of the movement. Earlier identity markers of adherence to scripture and doctrinally-based exclusivism have begun to fade as evangelicalism has become more fragmented and with the rise of newer, more Spirit-oriented subgroups. The paper introduces positive trends emerging in some parts of the evangelical movement due to internal angst, secularisation, and the holistic understanding of faith associated with the Lausanne Movement. Evangelicals now show increased openness to social involvement, learning from other Christian traditions, and cooperation in mission endeavours. The final section explores the potential for bridge building between evangelicalism and the Orthodox Church, framed by ideas from Gerard Hughes and Friedrich Schleiermacher. Although the paper can only credibly examine the evangelical end of the bridge, it is hoped that the general insights may benefit bridge builders at the Orthodox end also.